Analisis Bentuk dan Fungsi Unsur Negasi Dalam Struktur Sintaksis Antologi Puisi Chairil Anwar “Deru Campur Debu” (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the form and function of negation elements in the syntactic structure of Chairil Anwar's poetry anthology. The research method is descriptive qualitative with linguistic approach. The data sources are poetry texts by Chairil Anwar consisting of nine titles of Chairil Anwar's poems: Aku, Diponegoro, Karawang-Bekasi, Derai-Derai Cemara, Senja di Pelabuhan Kecil, Cintaku Jauh di Pulau, Hampa, Tak Sepadan and Siap Sedia. The data was collected using the documentation method, namely reading and scrutinizing the poetry texts to identify sentences that contain negation elements. The data found were then recorded and classified based on the form and location of the negation element in the syntactic structure of the sentence. Data analysis was conducted through several stages, namely: 1) identifying negation elements (all word/phrase elements containing negation elements in the poem); 2) classifying negation forms based on their types such as not, not, none, yet or don't; 3) analyzing syntactic structure (how the negation element functions in the syntactic structure, whether in predicate, subject, object or adverb; 4) interpreting the meaning and semantic and stylistic functions of negation elements in the context of the whole poem. To maintain data validity, this research uses theoretical triangulation by referring to various linguistic references (especially syntax and semantics) as well as previous studies on Chairil Anwar's poetry. In addition, data validation is done through cross-checking between readers on the results of identification and analysis. The results show that the element of negation plays a central role in shaping the syntactic structure, meaning and ideological and emotional character of his poetry.